2015
DOI: 10.1002/uog.14904
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of small-for-gestational-age neonates: screening by biophysical and biochemical markers at 19-24 weeks

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…The same group of investigators performed other studies in which sequential biophysical and biochemical screening, including uterine artery Doppler studies, and maternal mean arterial pressure were performed at 19 to 24 weeks and 32 to 36 weeks gestation to successfully predict a high proportion of SGA neonates. 13,25 Unfortunately, the combination of uterine artery Doppler studies with maternal clinical risk factors and serum biomarkers might be a prohibitive undertaking that limits its clinical applicability. Our study is different from previous studies in the following ways: 1) an unselected, general obstetrical population was recruited from multiple centers across the US; 2) appropriate cutoffs were determined for three different uterine artery measurements (diastolic notching, RI, and PI); 3) bilateral studies were performed in all patients, and the more abnormal result was used in the analyses, since uterine artery flow may be lower contralateral to placental location; 4) four outcomes were studied – SGA, gestational hypertension/preeclampsia, spontaneous preterm birth, and stillbirth; and 5) the analyses focused on the most clinically relevant aspects of the uterine artery studies – positive predictive values, areas under ROC curves, and likelihood ratios.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…The same group of investigators performed other studies in which sequential biophysical and biochemical screening, including uterine artery Doppler studies, and maternal mean arterial pressure were performed at 19 to 24 weeks and 32 to 36 weeks gestation to successfully predict a high proportion of SGA neonates. 13,25 Unfortunately, the combination of uterine artery Doppler studies with maternal clinical risk factors and serum biomarkers might be a prohibitive undertaking that limits its clinical applicability. Our study is different from previous studies in the following ways: 1) an unselected, general obstetrical population was recruited from multiple centers across the US; 2) appropriate cutoffs were determined for three different uterine artery measurements (diastolic notching, RI, and PI); 3) bilateral studies were performed in all patients, and the more abnormal result was used in the analyses, since uterine artery flow may be lower contralateral to placental location; 4) four outcomes were studied – SGA, gestational hypertension/preeclampsia, spontaneous preterm birth, and stillbirth; and 5) the analyses focused on the most clinically relevant aspects of the uterine artery studies – positive predictive values, areas under ROC curves, and likelihood ratios.…”
Section: Commentmentioning
confidence: 99%
“…3,913 In particular, models for predicting preeclampsia utilizing maternal clinical features, uterine artery Doppler studies, and maternal serum biomarkers are promising but may be too complex for widespread clinical application. 9,13,14 In one large retrospective cohort, uterine artery PI was able to predict 25 to 77 percent of growth-restricted babies delivering at various gestational ages at a ten percent false-positive rate, 15 while another observational study using biophysical (i.e., uterine artery Doppler studies) and biochemical markers at 19 to 24 weeks reported detection rates ranging from 100 to 42 percent for small for gestational age (SGA) neonates delivered before 32 weeks to greater than or equal to 37 weeks gestation, respectively. 13 However, the predictive value of uterine artery Doppler testing in unselected groups of pregnant women appears to be low in systematic reviews of previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[55] An algorithm whereby women who have moderate or high risk screening for SGA at 19–24 weeks are selectively offered further third trimester scanning at 32 and or 36 weeks has been proposed and now requires validation. [56]…”
Section: Discussionmentioning
confidence: 99%
“…The maternal-fetal Doppler evaluation conducted at 20–24 weeks of gestation is not universally accepted; however, available reports show that a mean UtA-PI >95 th percentile at this gestational age can identify women at risk of preeclampsia and of SGA 39,69 . The evaluation of two additional fetal Doppler parameters, the UA and the MCA, in combination with the EFW can improve the identification of fetuses at a higher risk of reduced size later in pregnancy.…”
Section: Discussionmentioning
confidence: 99%